(untitled) (Nordic Journal of African Studies, 2000)
This article deals with female primary education in Mali. Based on field work carried out in the village of Dougoukouna in 1997, it provides an analysis of the factors constraining girls’ schooling in a rural context. It argues that in order to fully understand the low participation of girls in Malian education one must consider not only the factors that are directly related to female status but also those of a more general kind. The article then examines the main types of constraint that influence female participation in Malian education. The socio-linguistic factors, such as the official status of a foreign language and the absence of a written environment, affect both boys’ and girls’ participation in education. Some of the factors related to the school environment, like the lack of school materials and inadequate teacher training, also influence the participation of both sexes, whereas others are closely related to the lack of female education. In particular, the socio-cultural and the socio-economic factors such as early marriage, religious beliefs and the lack of labour market opportunities are closely interwoven and they constrain above all education for girls.